A Comparative Study Of Environmental Sanitation And Environment-Based Diseases Among Suku Anak Dalam Community And General Community In Bungo Regency - Nahda Agustina; Dwi Noerjoedianto; Helmi Suryani Nasution; Ummi Kalsum; Rd Halim (International Journal of Health Engineering and Technology, 2025)
Based on data obtained from the Dwi Karya Bakti Village Midwife, the incidence of diarrhea was 6.27% and the incidence of skin diseases was 7.35% and 10.0% were affected by ISPA. These figures indicate that there are several Community residents who are still affected by diarrhea, skin diseases, and ISPA caused by a lack of environmental sanitation and unhealthy behavior in the SAD Community and the General Community. The study aims to determine the differences in environmental sanitation on the incidence of environmental-based diseases in the SAD Community and the General Community of Dwi Karya Bakti Village. Quantitative research with a comparative study design. The data sources or respondents in this study were the SAD Community and the General Community of Dwi Karya Bakti Village, with a sample size of 80 families. Data were collected through interviews using a questionnaire. The variables studied were toilet use, handwashing with soap, drinking water and food management, waste management, household wastewater management, and knowledge. Data analysis was descriptive and analytical using chi-square. The proportion of environmental-based diseases in SAD reached 57.5 while the General Community was 65.0%.